Business plans that work : a guide for small business - Zacharakis, Andrew; Spinelli, Stephen; Timmons, Jeffry A.; Timmons, Jeffry A. (New York : McGraw-Hill, 2011)
Business Plans That Work gives you an easy-to-follow template for conceptualizing, writing, focusing, and revising a business plan that converts your business idea into financial profit. --
A virtual blueprint for entrepreneurial success, this new edition of the popular entrepreneur's guide provides all the tools you need to communicate the value of your idea to investors, attract key talent, and create a plan you can turn to throughout the entire process of starting and running a business. You'll learn how to: --
Determine what to include in each plan, why, and for whom --
Secure the capital you need to get the project off the ground --
Assess opportunities and risks involved in your project --
Avoid common pitfalls that cost money, time, and effort --Book Jacket.
Entrepreneurs create the future -- Before you start planning, ask the right questions -- Getting started -- Industry : zoom lens on opportunity -- Company and product description : selling your vision -- Marketing plan : reaching the customer -- Operations and development : execution -- Team : the key to success -- The critical risks and offering plan sections -- Financial plan : telling your story in numbers.
Rev. ed. of: Business plans that work / Jeffry A. Timmons, Stephen Spinelli, Andrew Zacharakis. c2004.
Includes bibliographical references and index.
BSBA
Keywords: Business planning; Small business; Entrepreneurship